Relation Between Knowledge and Attitude Regarding DHF with PSN Behavior Among the Community Around the Campus - Kurniawan, Masnuh Eva; Mohamed, Ani Mazlina Dewi; Siyam, Nur; Fatikha, Nirmala; Fitriani, Nova Alvia (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
The city of Semarang as the capital of Central Java province is a DHF endemic city and has a high risk of dengue fever. Based on data from Central Java Provincial Health Office in 2015, DBD IR from 2012 to 2015 has increased. Dengue Hemorrhagic Fever (DHF) in the work area of Puskesmas Sekaran, Gunungpati in 2013 there are 7 cases of DHF patients, the highest number of Dengue fever is in Sukorejo Village with 6 patients then followed by Kelurahan Sekaran with 1 patient. The purpose of this study is to determine the relationship Knowledge and Public Attitudes about DHF with the Behavior Eradication Mosquito Nest (PSN) in the Village Sekaran Gunungpati District Semarang City. This type of research is observational analytics with cross sectional approach. The sample of this research is the community of Village Saving as many as 52 people. The research instrument used questionnaires and observation sheets. Data analysis using chi square test.The result of this research is that there is no correlation between knowledge about dengue behavior toward PSN behavior (p = 0,477) and there is no correlation between public attitudes about DBD on PSN behavior (p = 1,96). Conclusion from this research that there is no relation between knowledge and attitude of society about DBD to behavior of PSN DBD.